Improving Marketing Procedure of Fertilizer in AAV Company in Bulacan: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Developing a responsible circular economic value while working towards environmentally sustainable and inclusive products to meet the growing global demand is a challenging but crucial goal. This study aims to provide high-quality crops, essential raw materials, and products to manufacturing and other agriculture-related industries. The AAV company has shipped thousands of tons of fertilizer to various locations across the Philippines, serving businesses in different sectors, including freight forwarding and customs. The study utilized a qualitative descriptive method, and the respondents were employees and owners of the AAV company who encountered difficulties in their daily operations. The researchers conducted interviews to gather data. The respondents agreed with the proposed methods presented by the researchers as they believe they will be helpful and advantageous to the AAV company's marketing system in the future. The proposed procedures aim to create a more efficient and creative marketing system, including using online discussion platforms and creating ads to attract clients. The researchers suggested potential solutions such as application software and creative papers to improve the marketing system. Besides creating social media platforms, the AAV fertilizer company should maintain their good product and use more technology to attract more clients. The study suggests creating more ads and blogs to make the company more competitive internationally and keep up with strategies.
Keywords: Fertilizer; strategies; manufactured; sector; blogs; platform